Leukocyte Transcriptional Response in Sepsis. Issue 2 (August 2019) - Skibsted, Simon; Bhasin, Manoj K.; Henning, Daniel J.; Jaminet, Shou Ching; Lewandowski, Jeffrey; Kirkegaard, Hans; Aird, William C.; Shapiro, Nathan I.
ABSTRACT: Background: The complex host response to sepsis is incompletely understood. The aim of this investigation is to use leukocyte RNA sequencing to characterize biological functions, cellular pathways, and key regulatory molecules driving sepsis pathophysiology. Methods: This was a prospective, observational study of emergency department patients with sepsis, at an urban, academic, tertiary care center. In the derivation cohort, we collected blood at enrollment and 90 days after hospital discharge allowing each patient to serve as an internal control. We performed RNA sequencing to quantify transcriptional expression changes during sepsis and non-sepsis states. We then performed unsupervised and supervised analyses, as well as functional and pathway analyses. We selected the top down and upregulated genes and key regulatory molecules for validation. Validation occurred in a cohort of septic and non-septic using real-time PCR. Results: The derivation cohort included 5 patients, and RNA sequencing revealed 916 unique mRNA transcripts differentially expressed during sepsis. Among these, 673 (73%) genes were upregulated, and 243 (27%) were downregulated. Functional enrichment analysis revealed a highly dynamic downstream effect of the transcriptional activity during sepsis. Of the 43 functional cellular pathways activated during sepsis, the top pathways were closely associated with inflammation and response to infection. Validation occurred in 18 septic and 25 non-septic control patients, with 34/45 (76%) of identified genes validated. The regulatory analysis identified several key regulators of sepsis. Conclusions: Highly dynamic transcriptional activity occurs in leukocytes during sepsis, activating key cellular pathways and master regulatory molecules that drive the sepsis process. Abstract : Supplemental Digital Content is available in the text